The Development of Psychiatric Medication Monitoring System in Schizophrenia Patients, Chiang Khan Hospital. - Buaphuean , Sarawut (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This research employed a mixed-methods approach, utilizing both quantitative and qualitative methodologies, conducted in three phases: 1) a situational analysis, 2) the design and development of a psychiatric medication monitoring system for schizophrenia patients, and 3) an evaluation of the system’s effectiveness. The objective was to develop a psychiatric medication monitoring system for schizophrenia patients at Chiang Khan Hospital. Purposive sampling was used to select 1) 30 individuals comprising 15 psychiatric staff from sub-district health promotion hospitals and 15 village health volunteers, 2) 30 family members of schizophrenia patients, and 3) 30 schizophrenia patients. Data collection tools included 1) focus group discussions to examine problems, models, needs, and goals in psychiatric clinics, 2) focus group discussions to assess the appropriateness and problems of the monitoring system, 3) the Medication Adherence Scale for Thais©, and 4) an overall capability assessment. Data were analyzed using content analysis, percentage, mean, standard deviation, and paired t-tests. The results showed that 1) The mean medication adherence score before and after implementing the system was 26.23 (SD = 3.65) and 35.87 (SD = 2.65), respectively, with a statistically significant difference (p < 0.05). 2) The mean overall capability score before and after implementation was 55.03 (SD = 5.27) and 82.78 (SD = 9.32), respectively, with a statistically significant difference (p < 0.05). These findings suggest that the developed system can effectively enhance medication adherence and help patients better manage their psychiatric symptoms. Therefore, it is recommended that the system be adapted to local contexts and that patient records be integrated into an online system to improve service quality and patient monitoring.